HUBUNGAN ANTARA DISTRESS DAN DUKUNGAN SOSIAL DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA DALAM MENYUSUN SKRIPSI - Andarini, Sekar Ratri; Fatma, Anne (Universitas Sahid Surakarta, 2013)
Delay the preparation of the thesis can be regarded as academic procrastination, which is kind of delays that made the tasks related to formal academic (Joseph Ferrari, 1995). Students who feel distress and perform procrastination of the thesis work, need to get support from the people around him. The purpose of this study to determine the relationship between social support to students with academic procrastination in writing his thesis. Subjects in this study Sahid University of Surakarta student in 2005-2007 and the forces working on thesis or final project. Sampling was purposive sampling with the measuring tool of procrastination scale, scale stress and social support scale. Based on calculations between social support variables with the variable academic procrastination obtained a correlation coefficient (r) 0.603, p = 0.000 (p <0,05). While distress variables with academic procrastination variable obtained correlation coefficient (r) of 0.318, p = 0.046 (p <0,05). The results showed there was a significant negative relationship between social support with academic procrastination